Influence of urbanization on the role and status of husband and wife in the Tswana family - Motshologane, Samuel Rantshabele (My University, 1974)
Refer to the document
Thesis (M. A. (Sociology)) -- University of the North, 1974
Keywords: Family; Urbanization; Rural Tswana families; Families -- South Africa -- Pilansberg Region; Families -- South Africa -- Pretoria Suburban Area; Tswana (African people) -- Kinship -- South Africa; Husband and wife -- South Africa -- Pretoria Suburban Area -- Social life and customs; Husband and wife -- South Africa -- Pilansberg Region -- Social life and customs